Fault plane picking from focal mechanisms in reverse faulting stress: Application to the Mw6.9 Boumerdes (Algeria) earthquake sequence - Ouyed, Reda (2022)
Identification of the fault plane from two nodal planes of the focal mechanism is, in general, ambiguous. This problem is commonly solved using other constraints provided by tectonic, geological or seismic studies. In this paper, we evaluate the probability of identifying the fault plane using knowledge of stress field. We employ two alternative methods: (1) the slip angle method (SA), and (2) the highest instability method (IS). First, the efficiency of the methods was tested on synthetic data consisting of focal mechanisms compatible with a reverse stress regime. The tests revealed that the fraction of faults correctly picked by the IS method is higher than that of the SA method, particularly for large noise values. Second, the methods were applied to the aftershocks of the Boumerdes (Algeria) earthquake of May 21, 2003. This application showed that when taking into account the focal solutions for which the fault planes are determined using the IS method with a high probability, we observe consistency between the selected faults and the tectonics of the study area.